Factors associated with sleep duration among pupils. Issue 6 (23rd June 2020) - Kohyama, Jun; Ono, Makoto; Anzai, Yuki; Kishino, Ai; Tamanuki, Keita; Moriyama, Kengo; Saito, Yoko; Emoto, Runa; Fuse, George; Hatai, Yoshiho
Abstract: Background: Sleep shortage has been pervasive among pupils. Methods: Multiple regression analysis was used to analyze 2, 722 questionnaires obtained from grade 5 to 12 pupils, to determine factors associated with sleep duration. Results: Significant regression formulae for sleep duration were obtained for all school types: adjusted R 2 / P value were 0.14/<0.001 for elementary school; 0.11/<0.001 for junior high school; 0.06/<0.001 for high school. Longer after‐school activities (standardized regression coefficient/ P value were −0.22/<0.001 for elementary school; −0.10/<0.01 for junior high school; −0.18/<0.001 for high school) and more sleepiness (−0.09/<0.001 for elementary school; −0.07/<0.05 for junior high school; −0.07/<0.05 for high school) were significantly associated with reduced sleep duration for all school types. In both elementary and junior high schools, the higher grade (−0.53/<0.001 for elementary school; −0.10/<0.01 for junior high school), and longer weekday screen time (−0.15/<0.001 for elementary school; −0.19/<0.001 for junior high school) were also significantly associated with sleep loss. In elementary school, irregular dinner (−0.07/<0.05), breakfast skipping (−0.11/<0.001), longer weekend screen time (−0.09/<0.05) and better self‐reported academic performance (0.07/<0.05) also revealed significant associations with sleep loss. In high school, reduction of sleep duration was also significantly associated with higher standardized body mass index (−0.08/<0.05). Conclusions: Excessive after‐school activity might be considered in association with pupils' sleep reduction.